Social Media and its Impact on the Generation Z's Confident Character - Najmudin, Najmudin; Suja'i, Suja'i; Ma'zumi, Ma'zumi; Ilmiah, Wardatul; Aziz, Abdul (Jurnal Pendidikan Karakter JAWARA (Jujur, Adil, Wibawa, Amanah, Religius, Akuntabel), 2023)
This research aims to determine the effect of social media on the self-confident character of the Generation Z. The object of this research is Generation Z who study at Madrasah Tsanawiyah Al-Kairiyah Kubang Puji and Madrasah Al-Khairiyah Pontang. The total sample was 60 Generation Z, students are studying at Madrasah Tsanawiyah Al-Kairiyah Kubang Puji and Madrasah Tsanawiyah Al-Khairiyah Pontang. The sample was taken based on Ferdinand's sampling theory. The research method used is quantitative. The data collection method used a questionnaire, which was distributed to 60 Generation Z ,people who study at these two Madrasas. Data were processed using SPSS software version 26. Data analysis used a simple linear regression method. The results of this research show that social media positively and significantly effects formation of the confident character of the generation Z. The influence that social media variables have on the character of the generation Z is 17.9%. while the rest is influenced by other factors not examined in this study.